UNDERSTANDING THE CHILD SOLDIER IN UZODINMA IWEALA’S NOVEL, BEASTS OF NO NATION - Yeboah, Philomena Ama Okyeso; Otoo, Paul; Freitas, Philip Kwame; Bonku, Lucy Korkoi; Issaka, Charity Azumi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
The academic space has witnessed in recent times, a plethora of research works on child soldiering. However, the majority of these works are often viewed from a non-literary perspective. Using textual analysis which is purely qualitative in nature, this paper, from a literary perspective, focused on examining the representation of the child soldier figure in Iweala’s Beasts of No Nation by paying particular attention to the characterization of the child soldier as an individual who transitions from a victim of war to a victimizer. With the help of the trauma theory, the paper discussed and provided an understanding of the physiological factors and reactions that necessitate this transition. Based on Bloom’s concepts of trauma and the general theory of trauma, the paper finds that the child soldier transitions from a victim of war to a victimizer is a result of the fear that overwhelms him. Again, the child soldier undergoes this transition in order to survive the war – anarchetypal mammalian survival response. This study is significant as it has contributed to the existing literature on child soldier narratives in Africa and provided an understanding of the child soldier’s reactions and responses to the devastating trauma that accompanies war.